2022
DOI: 10.1111/ceo.14177
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year corneal cross‐linking outcomes: A Save Sight Keratoconus Registry Study

Abstract: Background: We aimed to determine the long-term outcomes of epitheliumoff cross-linking (CXL) in keratoconus patients.Methods: An observational registry study from 41 centres across 5 countries was carried out. Primary outcomes included the mean change in visual acuity (VA), Kmax, K2, and thinnest corneal thickness (TCT) at 1-5 years. Secondary outcomes included the percentage of eyes with worsening, stable and improving outcomes.Results: There were 976 eyes of 794 patients with 1-year of complete follow-up, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…project that tracks real-world treatment outcomes of keratoconus. [11][12][13][14] This study included patients from 24 sites in Australia, New Zealand, and Italy.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…project that tracks real-world treatment outcomes of keratoconus. [11][12][13][14] This study included patients from 24 sites in Australia, New Zealand, and Italy.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Cross-linking is an effective procedure for stabilizing corneal ectasia. 2,3 However, there is a risk of scarring and haze in a small population of patients, which increases its risk in this particular subgroup. Treating clinically significant haze remains a challenge for physicians as there is a lack of noninvasive treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…1 Epithelium-off corneal cross-linking (CXL) is the gold standard treatment to halt the progression of keratoconus through biomechanical stabilization of the cornea. 2,3 Clinically significant haze is a potential complication of CXL and occurs in 8.6% to 15.1% of patients who undergo CXL for progressive keratoconus. 2,4 This clinically significant haze differs from the mild transient haze associated with the normal healing process of CXL.…”
mentioning
confidence: 99%
“…It has been demonstrated that outcomes can continue to change over time in CXL such that future studies should include medium to long-term outcomes. Recently, the five-year CXL outcomes were published from the Save Sight Keratoconus Registry which showed CXL was effective in stabilizing keratoconus up to 5 years in most patients [ 60 ]. This systematic review and meta-analysis were limited by the quality of the studies included, heterogeneity, biases, small sample size, and short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%